Collaborative enhancement of luminous efficacy and fracture toughness based on interface design of Al2O3/YAG:Ce3+ eutectic phosphor ceramic grown by laser floating zone melting. Issue 7 (1st April 2022) - Liu, Yuan; Su, Haijun; Lu, Ze; Shen, Zhonglin; Guo, Yinuo; Zhao, Di; Liu, Haifang; Xie, Keyu; Huang, Taiwen; Yang, Wenchao; Yang, Min; Zhang, Jun; et al.
Abstract: A solid-state light source of directionally solidified Al2 O3 /Y3 Al5 O12 :Ce 3+ (YAG:Ce 3+ ) eutectic phosphor ceramic with superior luminous efficacy (∼116.48 lm/W) and high fracture toughness (∼4.0 MPa·m 1/2 ) is fabricated by laser floating zone melting (LFZM) for white light emitting diodes (WLEDs). The CeO2 -doped Al2 O3 /YAG eutectic ceramic presents improved fracture toughness and prevents from the pore formation as compared to the undoped eutectic ceramic. Impressively, the doping of Ce element and the diffusion coefficient play dominant roles in accelerating the formation of cellular structure and causing the enlargement of the eutectic lamella spacing, respectively. Moreover, the optimal phase interface design act as scattering center and enhance the light conversion efficiency. The maximum luminous efficacy is achieved under the comprehensive investigation of the eutectic structure, phase interface as well as Ce 3+ dopant. Moreover, the eutectic phosphor ceramic also exhibits excellent capability of thermal self-managing. The as-designed Al2 O3 /Y3 Al5 O12 :Ce 3+ eutectic phosphor ceramics have great potential as structural and functional materials in the high-brightness application of WLEDs.